Analisis Kuat Tekan Dan Kuat Lentur Beton Akibat Reduksi Semen Dengan Silicafume Dan Penggunaan Pasir Besi Dengan Zat Tambah Superplasticizer - Aryanto Kadang Kassa; Syahrul Sariman; Eka Yuniarto (Program Studi Teknik Sipil Universitas Bosowa, 2026)
The construction industry is currently facing several challenges, one of which is the increasing use of cement in large quantities which also has a negative impact on the environment. To overcome these challenges, one solution that can be applied is to reduce cement in the concrete mixture. Cement reduction can be done by using pozzolanic materials such as silica fume. In addition to silica fume, the use of iron sand can also be a good alternative to reduce the use of silica sand in the concrete mixture. In this study, a normal concrete compressive strength design of 25 MPa was used with the mixing method carried out by partial replacement of cement by silica fume by 10% accompanied by substitution of sand and iron sand of 10%, 20% and 30% respectively and the addition of 2% superplasticizer. This study shows that the addition of 2% superplasticizer can increase the compressive strength of concrete using iron sand material. The compressive strength of concrete using 10% iron sand is 25.57 MPa, for 20% it is 26.42 Mpa and for 30% it is 27.48 MPa. For flexural strength also experienced an increase of 10% by 4.53 MPa, 20% by 4.80 MPa and 30% by 5.00 MPa. This study shows that partial replacement of cement with silica fume and the use of iron sand to concrete as a whole causes an increase in compressive strength and flexural strength with the addition of 2% superplasticizer for all percentages.